A cartografia no contexto escolar de estudantes com deficiência visual: da exploração tátil do espaço à representação do lugar (escola) - Almeida, Adriana Leão Machado (2021)
This research intends to analyze the possible contributions of the tactile exploration of space to the construction of mental maps and the representation of the place (school). In this context, emphasizing the importance of tactile cartography for the elaboration of mental maps, made by students with visual impairments, the research participants were three blind students of basic education in the city of Feira de Santana, who accepted to participate voluntarily in this study. For the development of the research, the concepts of inclusive education, tactile cartography and mind map were the basis for the discussions presented. The ideas of Vygotsky (1983) and Ochaita and Rosa (1995) underpin discussions about inclusive education for students with visual impairments. From the same point of view Ribeiro (2008; 2011; 2012; 2016) and Loch (2008) supported the studies on tactile cartography. The methodological option selected was qualitative research, of the action-research type. In the meantime, semi-structured interviews, participant observation and tactile cartographic record of the mental map of the place were used for the production of data. The results show that the tactile exploration of space contributes significantly to the construction of mental maps, made by blind students, as well as to orientation and mobility.